Novel Cardiovascular Biomarkers Associated with Increased Cardiovascular Risk in Women With Prior Preeclampsia/HELLP Syndrome: A Narrative Review - Esmee ME Bovee; Martha Gulati; Angela HEM Maas (European Cardiology Review)
Evidence has shown that women with a history of preeclampsia or haemolysis, elevated liver enzymes and low platelets (HELLP) syndrome have an increased risk of cardiovascular disease later in life. Recommendations for screening, prevention and management after such pregnancies are not yet defined. The identification of promising non-traditional cardiovascular biomarkers might be useful to predict which women are at greatest risk. Many studies are inconsistent and an overview of the most promising biomarkers is currently lacking. This narrative review provides an update of the current literature on circulating cardiovascular biomarkers that may be associated with an increased cardiovascular disease risk in women after previous preeclampsia/HELLP syndrome. Fifty-six studies on 53 biomarkers were included. From the summary of evidence, soluble fms-like tyrosine kinase-1, placental growth factor, interleukin (IL)-6, IL-6/IL-10 ratio, high-sensitivity cardiac troponin I, activin A, soluble human leukocyte antigen G, pregnancy-associated plasma protein A and norepinephrine show potential and are interesting candidate biomarkers to further explore. These biomarkers might be potentially eligible for cardiovascular risk stratification after preeclampsia/HELLP syndrome and may contribute to the development of adequate strategies for prevention of hypertension and adverse events in this population.